2019
DOI: 10.1055/s-0039-1694741
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Regional Anesthesia in Extremity Reconstruction

Abstract: Background Regional anesthesia (RA) may help to circumvent the well-documented risks associated with general anesthesia, increase patient comfort and satisfaction, and mitigate costs. This study aims to investigate the utility of RA in extremity reconstruction. Methods The American College of Surgeons National Surgical Quality Improvement Program database was queried for all cases of extremity reconstruction including muscle, myocutaneous, or fasciocutaneous flaps from 2005 to 2016. Two groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This emphasizes the need for additional research, especially since one of the few other available studies by Weisberger et al, conducted on upper and lower extremity reconstructions, displayed a similar tendency of (non-significant) increased complications in regional anaesthesia patients compared to general anaesthesia alone. 15 A study by Jayaram et al on the use of spinal and epidural anaesthesia in lower extremity reconstructions also concluded that regional anaesthesia was a risk factor for flap failure. 7 Details on the review of the available literature are summarized in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes the need for additional research, especially since one of the few other available studies by Weisberger et al, conducted on upper and lower extremity reconstructions, displayed a similar tendency of (non-significant) increased complications in regional anaesthesia patients compared to general anaesthesia alone. 15 A study by Jayaram et al on the use of spinal and epidural anaesthesia in lower extremity reconstructions also concluded that regional anaesthesia was a risk factor for flap failure. 7 Details on the review of the available literature are summarized in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…There is only limited and, in part, conflicting evidence focusing on the effects of regional anesthesia on perfusion, specifically, microcirculation in the field of reconstructive microsurgery. Whereas regional anesthesia appears favorable for reconstructive procedures by means of the aforementioned effects and is generally considered safe, only a few studies were conducted to assess circulatory changes in free tissue transfer due to this anesthetic procedure [ 27 , 28 ]. Moreover, some authors already questioned the advantages of regional anesthesia, for example, in epidural/peridural techniques, based on its resultant changes in general blood flow distribution with consecutive risk of steal-phenomena [ 29 ].…”
Section: Discussionmentioning
confidence: 99%